2003
DOI: 10.1108/01437730310494284
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence and transformational leadership in retailing

Abstract: This study examines the relationship between emotional intelligence (EQ) and transformational leadership in the context of a UK-based retailing organisation and examines whether a relationship exists between store manager performance and EQ profiles. It identifies a discrepancy between the organisation's idealized leader success criteria and the average profiles derived from its current cohort of store managers. The results show a strong connection between the theory of EQ and transformational leadership: howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 9 publications
1
52
0
Order By: Relevance
“…Kuratko [35] asserted that motivational and self-influence constructs, such as emotional intelligence, are closely relevant to the concept of self-leadership. Emotional intelligence within the present context is defined as a set of cognitive capabilities and self-efficacy that enable individuals to monitor their own feelings and emotions, apart from understanding how such feelings or emotions can be distinguished from those of others, and thereby, the output information can be used to guide their emotions and thinking as they explore business ventures [63][64][65][66]. According to Nanayakkara, Wickramasinghe, and Samarasinghe [67], leaders with a higher level of emotional intelligence are more likely to reap higher profits.…”
Section: Emotional Intelligence and Micro-enterprise Performancementioning
confidence: 99%
“…Kuratko [35] asserted that motivational and self-influence constructs, such as emotional intelligence, are closely relevant to the concept of self-leadership. Emotional intelligence within the present context is defined as a set of cognitive capabilities and self-efficacy that enable individuals to monitor their own feelings and emotions, apart from understanding how such feelings or emotions can be distinguished from those of others, and thereby, the output information can be used to guide their emotions and thinking as they explore business ventures [63][64][65][66]. According to Nanayakkara, Wickramasinghe, and Samarasinghe [67], leaders with a higher level of emotional intelligence are more likely to reap higher profits.…”
Section: Emotional Intelligence and Micro-enterprise Performancementioning
confidence: 99%
“…And that is a true measure of great leadership. Leaders must create an environment where all team members can positively contribute to identify process improvement opportunities or highlight corrective activities to ensure that maximum team performance is achieved (Duckett & Macfarlane 2003).…”
Section: Leadership Training and Delivery Prospect: A Review Of Litermentioning
confidence: 99%
“…Many studies have found that leaders' emotional intelligence explains a high proportion of variance in leadership effectiveness and a variety of organizational outcomes (e.g., Carmeli, 2003;Ozcelik et al, 2008). A significant range of literature also provides empirical evidence to support the notion that emotional intelligence is a predictor of transformational leadership (Barbuto and Burbach, 2006;Leban and Zulauf, 2004;Mandell and Pherwani, 2003;Duckett and Macfarlane, 2003). Despite all the evidence supporting the positive value of emotional intelligence on leadership, several studies have produced contradictions regarding the necessity of emotional intelligence for leadership behavior, practices or effectiveness by arguing that more data based on defensible methodologies are needed to prove the validity of the EI/leadership link (Antonakis, 2003;Antonakis et al, 2009;Locke, 2005).…”
Section: Introductionmentioning
confidence: 99%